Participation of women according to Law No 8 year 2012 about the election of DPR RI, DPD, DPRD in Semarang City - Pangestika Rusadi Putri; Susi Sulandari (Journal of Public Policy and Management Review, 2019)
The role of women in politics are still said to be difficult. Women and politics is difficult to achieve in Indonesia, the cause that is there is a culture that is growing in the community that the man responsible for finding the earnings and only responsible to take care of the child. By participating in the legislative elections could be one way for women to get into politics and eventually the interests of women would be represented. But the Law Number 8 year 2012 about the election of DPR RI, DPD, DPRD of women's legislative candidates remained rarely to be elected the legislative. The purpose of this research is to analyse the level of women's participation in the implementation of Law No. 8 year 2012 and describes the factors that inhibit women to participate. This research uses qualitative research types. Data collection techniques used were used observations and interviews. The analysis of the data is done through data collection, reduction of data, display data as well as the withdrawal of the conclusion. The results showed that women in the Semarang City had given her participation in fulfillment of a 30% representation of women but her participation is still low because there are still women who do not participate directly but only participate by supporting one of the parliamentary candidates only and still many women vii who do not know about the existence of this provision. The advice given that is making a small Committee as dealer information and aspirations, to educate women and their families about the benefits of women plunge into the world of politics and women more approach to surrounding residents.